Quantum Mechanics of Charged Particle Beam Optics : Understanding Devices from Electron Microscopes to Particle Accelerators - Jagannathan, Ramaswamy; Khan, Sameen Ahmed (Boca Raton, FL : CRC Press, 2019)
Classical Charged Particle Beam Optics used in the design and operation of all present-day charged particle beam devices, from low energy electron microscopes to high energy particle accelerators, is entirely based on classical mechanics. A question of curiosity is: How is classical charged particle beam optics so successful in practice though the particles of the beam, like electrons, are quantum mechanical? Quantum Mechanics of Charged Particle Beam Optics answers this question with a comprehensive formulation of Quantum Charged Particle Beam Optics' applicable to any charged particle beam device.
OCLC-licensed vendor bibliographic record.
Keywords: Quantum optics; SCIENCE / Physics / Optics & Light; SCIENCE / Physics; TECHNOLOGY / Electricity; TECHNOLOGY / Lasers